brief review of the Mining concession for exploration and explotation froM the legal view point - Gutiérrez, Ilián (2014)
According to the General Mining Law, eight different types of mining activities are development in Peru, with the exception of mining prospecting, prospecting and mining marketing that are free others require of a Mining Concession. In that sense, this paper will seek to develop the legal nature of mineral exploration and exploitation concession, through its legal treatment of history, and especially to explain it not only has the character of an administrative act, but which in turn gives a real right. We have observed that we live in a country whose main economic activity is mining, however legal institutions relating to it are poorly developed and this is not due to a lack of legislative regulation of such activity, but by the lack of interest lawyers, rather than the time and economic development has been responsible change.